(untitled) (Applied Biological Research, 2023)
The development of current healthcare system is greatly influenced by plants having therapeutic potential, especially the medicinal plants. The advent of new ailments worldwide has encouraged the researchers to explore the potential of different plant parts as well. The research aims to compile information on Calotropis procera traditional usage and biological activity from a native population in the northern Nigeria, Kaduna state. Random sampling was employed for the collection of traditional medicinal knowledge on C. procera. Radical scavenging activity, ferric reducing antioxidant power, and disk diffusion assay was employed to evaluate its biological activity of ethanol and aqueous extracts of C. procera. The study revealed that C. procera is traditionally used in the area to treat a variety of ailments like hypertension, migraine, and spiritual problems having the highest fidelity at 0.9%. The leaves exhibited highest radical scavenging, ferric reducing power, and antibacterial activity at 86.01 µg ML-1 and 18.1 mmol g-1. The largest zone of inhibition against Pseudomonas aeruginosa was found in an ethanol leaf extract of C. procera at 23.5 mm. The study revealed the leaf of C. procera as a good avenue for the development of modern drugs.